Kappa opioid receptors in the central amygdala modulate spinal nociceptive processing through an action on amygdala CRF neurons - Ji, Guangchen (Mol Brain, 2020)
The amygdala plays an important role in the emotional-affective aspects of behaviors and pain, but can also modulate sensory aspect of pain (“nociception”), likely through coupling to descending modulatory systems. Here we explored the functional coupling of the amygdala to spinal nociception. We found that pharmacological activation of neurons in the central nucleus of the amygdala (CeA) increased the activity of spinal dorsal horn neurons; and this effect was blocked by optogenetic silencing of corticotropin releasing factor (CRF) positive CeA neurons. A kappa opioid receptor (KOR) agonist (U-69,593) was administered into the CeA by microdialysis. KOR was targeted because of their role in averse-affective behaviors through actions in limbic brain regions. Extracellular single-unit recordings were made of CeA neurons or spinal dorsal horn neurons in anesthetized transgenic Crh-Cre rats. Neurons responded more strongly to noxious than innocuous stimuli. U-69,593 increased the responses of CeA and spinal neurons to innocuous and noxious mechanical stimulation of peripheral tissues. The facilitatory effect of the agonist was blocked by optical silencing of CRF-CeA neurons though light activation of halorhodopsin expressed in these neurons by viral-vector. The CRF system in the amygdala has been implicated in aversiveness and pain modulation. The results suggest that the amygdala can modulate spinal nociceptive processing in a positive direction through CRF-CeA neurons and that KOR activation in the amygdala (CeA) has pro-nociceptive effects.